The Russian Federation in Transition : External Developments - Christensen, Benedicte (Washington, D.C. : International Monetary Fund, 1994)
This paper examines the effects of three "shocks" - the disintegration of the U.S.S.R., domestic economic reform, and changing relations with other countries- on Russia's balance of payments position. The importance of consistent economic reform and a liberal trade regime is stressed, together with the role of financial assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet